THE INFLUENCE OF PRICE PERCEPTION, ONLINE CUSTOMER RATING, AND TRUST ON PURCHASE DECISIONS - Syahna Syahanda Akbar; Kristina Anindita Hayuningtias (SEAN Institute, 2023)
This study aimed to analyze the effect of each independent variable on price perception, online customer rating, and trust in purchasing decisions. The method used in this research is quantitative. The population in this study are consumers who use the Shopee Food application in Semarang and have previously purchased at least 1 time. with a sample of 100 Respondents were determined using purposive sampling. The data analyzed were primary data collected through a questionnaire. Based on the F test, all independent variables simultaneously affected purchasing decisions. The t-test and multiple regressions show that the price perception variable has a positive and significant effect on purchasing decisions, the online customer rating variable has a positive and significant effect on purchasing decisions, and the trust variable has a positive and significant effect on purchasing decisions.